Analisis percakapan pada unggahan berbasis Artificial Intelligence akun Instagram Kementerian Luar Negeri Ukraina - Budiharjo, Slamet; Putranto, Algooth (Magister of Communication Science, Sahid University Jakarta., 2024)
ABSTRACT The presence of Artificial Intelligence (AI) has brought many changes to human life. Many job conveniences have been helped by the development of AI. Jobs that previously could be completed by humans are slowly starting to be replaced by entities called AI. The use of AI technology brings various innovations and efficiencies, for example content personalization to create interesting and relevant content for users, account automation, and so on. The Ministry of Foreign Affairs of Ukraine uses AI as a provider of up-to-date and reliable information on consular affairs. The post on the Instagram account of the Ukrainian Ministry of Foreign Affairs stated that Victoria Shi would carry out the task of providing various information services to the public and media as well as Ukrainian consular affairs services. There were mixed reactions to the upload, many responded positively, although quite a few also responded negatively in the comments column. This research aims to describe, understand and analyze the content of conversations or texts and the use of emoticon symbols that occur in the Instagram posts of the Ministry of Foreign Affairs of Ukraine by paying attention to aspects such as the structure of speech transfer, construction of the exchange of ideas, parts of speech and identity. Analysis by paying attention to the form of conversation and interaction that occurs as a form of study in the field of communication.Keywords: Artificial Intelligence, social media, Ukraine, conversation